Development of Interactive E-Modules in Science Learning Courses for Early Childhood: Training Students’ 21st Century Skills - Handayani, Peny Husna; Eza, Gita Noveri; Sari, Winda Widya (Journal of Natural Science and Integration, 2024)
Today's learning certainly needs to keep up with the times where the demands of the times are not only knowledge, but also 21st century life skills, which include the ability to think critically, creativity, cooperation and communication. The aim of this research is to produce an interactive e -module in the Science Learning for Early Childhood course as an interactive learning medium and resource to help train and improve students' 21st century skills. This research is ADDIE development research which consists of five steps, namely analysis, design, development, implementation and evaluation. The sample in this study was 150 students taking Science Learning courses for early childhood. This e-module was validated by four experts then analyzed using the Aiken formula, and showed a validity value of 0.844 in the high validity category. Next, an independent sample t-test was conducted to see the difference in treatment of 21st century skills from the sample The results show that there is a difference significant difference between students who use interactive e-modules and those who do not use them, with a sig value (0.000) < α (0.05). This indicate that the development of this interactive e -module is effective for training students' 21st century skills, which consist of critical thinking, creativity, cooperation and communication skill. This interactive e-module for early childhood science learning can help student develop their 21st century skills. Keywords: interactive e-modul, 21st century skills (4C), science learning, early childhood, students